The Ability of Aquatic Carnivorous Plants Utricularia vulgaris L. as Heavy Metal Bioremediators - Su'udi, Mukhamad; Sururin, Fahma Wardah; Ardiyanti, Kurnia Dwi (Indonesia International Institute for Life Sciences, 2024)
Utricularia vulgaris is one of the aquatic carnivorous plants that is able to grow in low-nutrient environmental conditions. This unique plant is also a macrophytic plant whose entire body except for the flowers is submerged in water. Utricularia vulgaris also has no roots so it grows to float in water. The plant was found growing in an environment polluted by heavy metals. Several studies have shown that U. vulgaris is able to absorb several types of heavy metals effectively, such as Cu, Mn, Zn, and Fe. These heavy metals are needed in small amounts by organisms, but in high amounts they can inhibit the growth of aquatic organisms. Utricularia vulgaris, a carnivorous plant, has shown the potential to absorb heavy metals, making it a subject of interest for phytoremediation.